PENCEGAHAN DIABETES MELITUS MELALUI EDUKASI KESEHATAN PADA KADER KESEHATAN DI DUSUN KEYONGAN, BOYOLALI - Sutanta, Sutanta; Al Hasbi, Habid; Wulandari, Arif Dwi (Aspirasi Masyarakat, 2025)
Diabetes Mellitus (DM) is a chronic disease with a steadily increasing prevalence both globally and nationally. Indonesia has a high number of DM sufferers, which continues to grow annually. This situation demands community-based prevention efforts, one of which is through the empowerment of health cadres. This community service program, implemented in Keyongan Hamlet, Boyolali, aimed to improve the understanding and skills of health cadres in recognizing risk factors, early signs, and prevention strategies for DM. The activity method consisted of interactive counseling combined with group discussions and the use of leaflets. The activity took place on January 20, 2025, with 30 participants. Evaluation was conducted in a participatory manner, both through active participant involvement in the discussion and direct feedback. The results of the activity showed an increase in cadre knowledge, particularly regarding the importance of a healthy lifestyle, diet management, physical activity, and early detection. Community-based education has proven effective as a promotive and preventive measure, and strengthens the role of cadres in supporting public health.